TEG011 persistence averts extramedullary tumor growth without exerting off-target toxicity against healthy tissues in a humanized HLA-A*24:02 transgenic mice. Issue 6 (5th February 2020) - Johanna, Inez; Hernández-López, Patricia; Heijhuurs, Sabine; Bongiovanni, Laura; de Bruin, Alain; Beringer, Dennis; van Dooremalen, Sanne; Shultz, Leonard D.; Ishikawa, Fumihiko; Sebestyen, Zsolt; Straetemans, Trudy; Kuball, Jürgen
Abstract: γδT cells play an important role in cancer immunosurveillance and are able to distinguish malignant cells from their healthy counterparts via their γδTCR. This characteristic makes γδT cells an attractive candidate for therapeutic application in cancer immunotherapy. Previously, we have identified a novel CD8α-dependent tumor-specific allo-HLA-A*24:02-restricted Vγ5Vδ1TCR with potential therapeutic value when used to engineer αβT cells from HLA-A*24:02 harboring individuals. αβT cells engineered to express this defined Vγ5Vδ1TCR (TEG011) have been suggested to recognize spatial changes in HLA-A*24:02 present selectively on tumor cells but not their healthy counterparts. However, in vivo efficacy and toxicity studies of TEG011 are still limited. Therefore, we extend the efficacy and toxicity studies as well as the dynamics of TEG011 in vivo in a humanized HLA-A*24:02 transgenic NSG (NSG-A24:02) mouse model to allow the preparation of a first-in-men clinical safety package for adoptive transfer of TEG011. Mice treated with TEG011 did not exhibit any graft-versus-host disease-like symptoms and extensive analysis of pathologic changes in NSG-A24:02 mice did not show any off-target toxicity of TEG011. However, loss of persistence of TEG011 in tumor-bearing mice was associated with the outgrowth of extramedullary tumor masses as also observed for mock-treated mice. In conclusion, TEG011 is well tolerated without harming HLA-A*24:02 + expressing healthy tissues, and TEG011 persistence seems to be crucial for long-term tumor control in vivo.